2001
DOI: 10.1002/polb.1210
|View full text |Cite
|
Sign up to set email alerts
|

Investigation at the chain segmental level of the miscibility of poly(vinyl chloride)/atactic poly(methyl methacrylate) blends

Abstract: We employed high-resolution 13 C cross-polarization/magic-angle-spinning/ dipolar-decoupling NMR spectroscopy to investigate the miscibility and phase behavior of poly(vinyl chloride) (PVC)/poly(methyl methacrylate) (PMMA) blends. The spinlattice relaxation times of protons in both the laboratory and rotating frames [T 1 (H) and T 1 (H), respectively] were indirectly measured through 13 C resonances. The T 1 (H) results indicate that the blends are homogeneous, at least on a scale of 200 -300 Å, confirming the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Note that the peaks of the unlike pairs (PMMA/PVC) are higher than those of the like pairs (PMMA/PMMA, PVC/PVC). According to the assumption proposed by Mattice et al this suggests that the blend systems tend to be miscible, which agree with some experimental observations . Besides, as compared to the cases in the iPMMA/iPVC blend, the peaks of the like pairs in the sPMMA/iPVC blend are lower and those of the unlike pairs are higher.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Note that the peaks of the unlike pairs (PMMA/PVC) are higher than those of the like pairs (PMMA/PMMA, PVC/PVC). According to the assumption proposed by Mattice et al this suggests that the blend systems tend to be miscible, which agree with some experimental observations . Besides, as compared to the cases in the iPMMA/iPVC blend, the peaks of the like pairs in the sPMMA/iPVC blend are lower and those of the unlike pairs are higher.…”
Section: Resultssupporting
confidence: 87%
“…According to the assumption proposed by Mattice et al 2,52 this suggests that the blend systems tend to be miscible, which agree with some experimental observations. [53][54][55][56][57] Besides, as compared to the cases in the iPMMA/iPVC blend, the peaks of the like pairs in the sPMMA/iPVC blend are lower and those of the unlike pairs are higher. As explained in the previous work, 34 these results strongly support the experimental observation that sPMMA is more miscible with iPVC than iPMMA.…”
Section: Journal Of Polymer Sciencementioning
confidence: 99%
“…All these snapshots in this paper are plotted using the VMD tool. [ 41 ] It can be observed that, throughout the whole composition range, the PMMA/PVC blend exhibits one homogeneous phase where one component well disperses in another component, whereas the PMMA/PS blend undergoes phase separations forming heterogeneous systems, which are in excellent agreements with the experimental observations [ 24,[42][43][44][45][46][47] and the previously simulated results. [ 21,22,48 ] Note that our simulated systems are made According to other authors' works, [ 28,30,31 ] such chain length (i.e., 100 monomers) is long enough to model the realistic chains.…”
Section: Phase Morphologiessupporting
confidence: 86%
“…To ascertain the homogeneity of the blends, we investigated the relaxation behavior of protons. For the miscible polymer blends at the molecular level, protons of chemically different chains are closely coupled and relaxed at an identical rate through a spin‐diffusion mechanism; therefore, an examination of the relaxation behavior of protons can provide insight into the homogeneity of the system 21, 35–36. In this work, information about the scale of miscibility and the phase structure was examined with dynamic relaxation experiments through 13 C NMR CP‐MAS.…”
Section: Resultsmentioning
confidence: 99%